Peningkatan Kualitas Audit Internal Inspektorat Daerah dalam Mewujudkan Tata Kelola Keuangan Akuntabel - Susana Purnamasari Baso; Margareth J.P Hartono; Maria O. Sartin; Maria Angelina Mau Luma; Marlin Septianty Haki; Bellasinta Nova Jonas (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the influence of auditor competence, independence, and the use of audit technology on the quality of internal audits of Regional Inspectorates and their impact on the accountability of regional financial governance. Using a quantitative approach, this study involved 154 internal auditors from three regions who were analyzed using an explanatory survey method. The data analysis method used was multiple and simple linear regression to test the relationship between variables. The results showed that auditor competence had a positive and dominant influence on internal audit quality (β = 0.402, p = 0.000), independence also had a positive influence (β = 0.298, p = 0.000), while the use of audit technology had a limited positive influence (β = 0.187, p = 0.011). Furthermore, audit quality was proven to have a significant influence on the accountability of regional financial governance with a value of β = 0.588 and R² = 0.531. These findings confirm that better internal audit quality, influenced by higher auditor competence, strong independence, and more optimal utilization of audit technology, is a key prerequisite for achieving accountability in regional financial governance.